Changing microRNA Expression during Three-Month Wasp Venom Immunotherapy. (17th November 2019) - Specjalski, Krzysztof; Maciejewska, Agnieszka; Pawłowski, Ryszard; Zieliński, Maciej; Trzonkowski, Piotr; Pikuła, Michał; Jassem, Ewa
ABSTRACT: MicroRNAs are small non-coding molecules playing a significant regulatory role in several allergic diseases. However their role in tolerance induction remains unclear. The aim of this study was to determine the expression of selected microRNAs during the first three months of wasp venom immunotherapy (VIT). 5 adult patients with a history of severe systemic reactions after stinging by wasps and confirmed sensitization were included. Venous blood samples were collected before VIT, 24 hours after completing its initial phase and after 3 months of the maintenance therapy. A control group was comprised of 5 healthy individuals with no history of allergy. In the blood samples expression of 96 microRNAs was determined with the use of microfluidic cards. In a statistical analysis the expression was compared between the study groups as well as between the pre- and post-VIT samples. Significant differences were found between the patients with wasp venom allergy and the healthy controls in the expression of miR-601 and miR-1201 upregulated in allergic patients at every time point ( p = 0.04; p = 0.015, respectively). During VIT profile of microRNA was changing with lower expression of 6 microRNAs (including miR-182, miR-342, miR-375) and higher of 11 microRNAs (including let-7d, miR-34b, miR-143). To conclude, VIT has led to some changes in the expression of microRNA associated with Th2-type inflammation and tolerance induction.